Phenotypic Trait Variation as a Response to Altitude-Related Constraints in Arabidopsis Populations - Duruflé, Harold; Ranocha, Philippe; Mbadinga Mbadinga, Duchesse Lacour; Déjean, Sébastien; Bonhomme, Maxime; San Clemente, Hélène; Viudes, Sébastien; Eljebbawi, Ali; Delorme-Hinoux, Valerie; Sáez-Vásquez, Julio; Reichheld, Jean-Philippe; Escaravage, Nathalie; et al. (Frontiers in Plant Science, 2019)
Natural variations help in identifying genetic mechanisms of morphologically and developmentally complex traits. Mountainous habitats provide an altitudinal gradient where one species encounters different abiotic conditions. We report the study of 341 individuals of Arabidopsis thaliana derived from 30 natural populations not belonging to the 1001 genomes, collected at increasing altitudes, between 200 and 1800 m in the Pyrenees. Class III peroxidases and ribosomal RNA sequences were used as markers to determine the putative genetic relationships among these populations along their altitudinal gradient. Using Bayesian-based statistics and phylogenetic analyses, these Pyrenean populations appear with significant divergence from the other regional accessions from 1001 genome (i.e. from north Spain or south France). Individuals of these populations exhibited varying phenotypic changes, when grown at sub-optimal temperature (22°C vs 15°C). These phenotypic variations under controlled conditions reflected intraspecific morphological variations. This study could bring new information regarding the west European population structure of A. thaliana and its phenotypic variations at different temperatures. The integrative analysis combining genetic, phenotypic variation and environmental datasets is used to analyse the acclimation of population in response to temperature changes. Regarding their geographical proximity and environmental diversity, these populations represent a tool of choice for studying plant response to temperature variation.